Financial Screening in Criminal Cases—Impractical and Irrelevant - William H. Fortune (Washington University Law Quarterly, 1973)
This Article questions courts’ inquiry into a defendant’s financial situation in determining whether he is may have counsel provided for him without cost.
Keywords: Public legal service; Right to counsel